Think zebras!: when to suspect if your child has primary immunodeficiency disorder (PID) - Abu Bakar, Asrar (Malaysian Integrated Medical Professionals Association, 2024)
Infections during childhood are commonplace, with an average healthy child experiencing 4-8 infections annually. Exposure to various microorganisms while exploring the environment is a natural part of a child's development, crucial for immune system maturation and social interaction. However, a minority of children face challenges in immune system development, either due to genetic mutations causing Primary Immunodeficiency (PID) or secondary factors like chronic illnesses or immune-suppressing drugs.